2022
DOI: 10.4103/ijt.ijt_104_20
|View full text |Cite
|
Sign up to set email alerts
|

Light-Based Home-Use Hair Removal Devices

Abstract: Background: The use of light-based home-use hair removal devices has seen a significant increase in the last decade all over the world. Home-based devices would be especially more relevant in the context of the COVID-19 pandemic, with patients having less access to laser hair removal in clinics. This survey attempted to evaluate the practices-related use of light-based home-use hair removal devices in our region and also to assess patient satisfaction related to the same. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…There is a range of home-use laser devices including the Silk'n™ Flash & Go with a wavelength of 475-1200 nm [13,14]. The number of light-based home-use lasers available in the market has significantly increased since the COVID-19 pandemic when social distancing impacted non-essential medical services [15]. According to Austin et al (2021), home-use devices were identified to treat various conditions and concluded that all devices had favourable safety features with few significant side-effects, however, the limitations to the review included a limited amount of randomized controlled trails and a lack of data on the long-term efficacy and safety of the devices [16].…”
Section: Introductionmentioning
confidence: 99%
“…There is a range of home-use laser devices including the Silk'n™ Flash & Go with a wavelength of 475-1200 nm [13,14]. The number of light-based home-use lasers available in the market has significantly increased since the COVID-19 pandemic when social distancing impacted non-essential medical services [15]. According to Austin et al (2021), home-use devices were identified to treat various conditions and concluded that all devices had favourable safety features with few significant side-effects, however, the limitations to the review included a limited amount of randomized controlled trails and a lack of data on the long-term efficacy and safety of the devices [16].…”
Section: Introductionmentioning
confidence: 99%